ANALISIS KEWENANGAN INTERNATIONAL CRIMINAL COURT (ICC) PADA PENANGANAN KASUS PALESTINA MENURUT SUDUT PANDANG HUKUM PIDANA INTERNASIONAL - Purba, Martinius Rambe; Wiwi, Wiwi (Bhinneka Multidisiplin Journal, 2024)
An international criminal court (ICC) is a criminal court that is a permanent within international legal scope, which has competence try individuals on the basis of criminal acts of an international nature. These criminal acts include war crimes, genocide, evil on humanity, and aggression crime. International criminal courts were designed with the goal of mitigating the malaise of national judicial systems. In this context, the ICC will only carry out its functions and authority when the country's national courts are no longer able to invest and prosecute this form of crime. As a court established to handle and resolve international crime problems, ICC have a significant role in maintaining world peace. Therefore, the war conflict which happened in Palestine is one of the jurisdictions of the international criminal court to handle it